O impacto da Cidade Administrativa na mobilidade de trabalhadores na Região Metropolitana de Belo Horizonte - Ana Luiza de Aguiar Carneiro (2022)
Mobility is a fundamental aspect in the process of urbanization and metropolization, population concentration and deconcentration and the formation of urban centralities. The pattern and volume of movements can present different trends over time and are linked, among other factors, to economic and demographic dynamics. In this sense, it is expected that the creation of a new centrality in the Metropolitan Region of Belo Horizonte (RMBH), such as the Administrative City (CAMG), to concentrate the state Executive Branch, public administration bodies and entities, will have an impact on commuting movements. and interns due to work at the RMBH. In fact, CAMG transferred a large number of jobs, previously located in the center of the capital, to Vetor Norte, close to the municipal boundary with the municipalities in the northern fraction of the Metropolitan Region of Belo Horizonte. In this sense, the dissertation evaluates how the implementation of CAMG generated an impact on the commuting mobility of workers through the reordering of flows. Data and information from the period before and after the implementation of the public equipment were used, which was possible with the availability of data from the Origin-Destination (OD) surveys of the years 2002, 2012 and 2019. In this way, a characterization was made of commuting mobility patterns for the years of study and changes in the level and structure of mobility were identified. For this, measures similar to those of migration were used to observe the flows, being the Net Commuting Rate, which considers the entries and exits of commuters and observes the balance of movements in relation to the population, the Commuting Efficacy Index , checking the absorption or evasion potential of municipalities and Traffic Zones, the Pendular Flow Rate and Internal Flow of displacements for work reasons to the CAMG Zone, which weights the flows of each Zone or municipality by its population and the method log-linear from a total sum reference coding technique, which makes it possible to analyze the structure of mobility, its variation over time and the interaction between origins and destinations. The research allowed the identification of the impact of the Administrative City on commuting and internal mobility through indicators that showed a greater volume of flow received, mainly in the first period (2002-2012), from individuals from other municipalities and other Traffic Zones in Belo Horizonte.